TRANSFORMASI DIGITAL DAN MANAJEMEN SUMBER DAYA MANUSIA DI UNIVERSITAS DAN INSTANSI PUBLIK - Syaifudin Suhri Kasim; Muhamad Faza Almaliki; Sylsiani Mursalim; Ferima; Maudhy Satyadharma; Eko Wahyu Prasetyo (Yayasan Pendidikan Literasi Borneo, 2025)
Digital transformation has become a strategic necessity for universities and public institutions to address the dynamics of technological change and organizational performance demands. This study aims to analyze the role of digital leadership and strategic human resource management in supporting the success of digital transformation. The method used is a literature review with a narrative approach to various relevant studies in the education and public service sectors. The results of the study indicate that digital transformation in universities and public institutions is a systemic and gradual process that requires governance readiness, technology integration, and sustainable human resource development